Property of the Hilandar Monastery in Gornja and Donja Gadimlja - Zarković, Božidar V.; Gašić, Dejan R. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
A large portion of the property in the possession of the Hilandar Monastery is located in Kosovo and Metohija. Great benefactors of this and other monasteries in the Mount Athos were the members of the Branković family. The relations between them and the monastery were consolidated when Nikola Radonja, the oldest son of Branko Mladenović, became a monk there and was credited for the first donation. The contributions of the Branković family were located in Drenica, Kosovo, Lab, Metohija, Kosovsko Pomoravlje, and the area of Skopje. One of the donated lands, by Vuk Branković, was the territory of the two villages Gadimlja (Gornja and Donja). This property was situated in the south-east of the Kosovo plain, on the slopes of Mount Žegovac, a border area to the property of Prince Lazar and his heirs. The property was not large but its strategic value was great—it was placed on the main road from Priština to Skopje. The significance of this territory also comes from its position between the estate of the Lazarević family—on the north side, it was the Lipljan monastery land (El. metókhion) of the Hilandar tower (Ser. pirg) Hrusija, a land which was at one point confiscated by Prince Lazar for unpaid debts; while on the east side, it was Lazar’s gardens in the vicinity of Novo Brdo, in the districts of Topolnica, Morava, and Izmornik. This property was defined after the Battle of Kosovo, when Vuk Branković expanded his territory expecting to be free of the Ottoman rule. The detailed definition of the property allows us to precisely determine its boundaries. Most of the toponyms given in the Charter are preserved today in the same or slightly altered form.
Keywords: Gornja and Donja Gadimlja; Kosovo; Vuk Branković; Hilandar Monastery